2002
DOI: 10.1002/1521-3773(20021202)41:23<4378::aid-anie4378>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The Genesis of Molecular Electronics

Abstract: Molecular electronics is, relatively speaking, a young field. Even so, there have been many significant advances and a much greater understanding of the types of materials that will be useful in molecular electronics, and their properties. The purpose of this review is to provide a broad basis for understanding the areas where new advances might arise, and to provide introduction to the subdisciplines of molecular electronics. This review is divided into two major parts; an historical examination of the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
489
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 814 publications
(497 citation statements)
references
References 84 publications
1
489
0
1
Order By: Relevance
“…One particularly fascinating area is the application of switchable molecular building blocks in information storage. 88,89 In order to achieve this goal, however, a detailed understanding of the adsorption behaviour of large organic molecules on well-defined surfaces is essential, which has stimulated model investigations in an ultrahigh vacuum. A large number of studies have been performed using LT STM; this method not only allows for direct imaging of the adsorbed species in real space, but also opens up the possibility to manipulate the molecular objects.…”
Section: Conformational Switching Of Porphyrin Moleculesmentioning
confidence: 99%
“…One particularly fascinating area is the application of switchable molecular building blocks in information storage. 88,89 In order to achieve this goal, however, a detailed understanding of the adsorption behaviour of large organic molecules on well-defined surfaces is essential, which has stimulated model investigations in an ultrahigh vacuum. A large number of studies have been performed using LT STM; this method not only allows for direct imaging of the adsorbed species in real space, but also opens up the possibility to manipulate the molecular objects.…”
Section: Conformational Switching Of Porphyrin Moleculesmentioning
confidence: 99%
“…[154][156] [179] The concept of molecules as tailor made functional building blocks with atomic precision for electronic applications ranging from single molecules, [153] [253] through molecular devices, [254]- [258] to bulk materials leads to new challenges in organic chemistry. Of particular interest are conjugated systems as their delocalized electrons are expected to considerably favor electronic transport through their planer structures.…”
Section: Switchable Conducting Azo Biphenylsmentioning
confidence: 99%
“…2,3,7 Supramolecular arrays are of interest with respect to the study of energy transfer and photosynthetic mechanisms 7,8 while two-dimensional porphyrin assemblies have attracted attention for possible application as chemical sensors, in molecular electronics, or as chemically switchable 2D rotors. 3,9,10 Related to this, we recently showed that a porphyrin-functionalized silver surface exhibits ligand binding and unbinding reactions characteristic of the free metalloporphyrin 11 and showed that a well-chosen ligand can strongly alter the dynamics of adsorbed porphyrins. 10 Porphyrins have been attached to oxide surfaces for use as sensors by means of organophosphonate linkers.…”
Section: Introductionmentioning
confidence: 99%